Mathematics-Its 0rigin And Development - Rani, Mrs Rckha (Innovative Research Thoughts, 2017)
‘Ganita* which literally means the sciences of calculation, is the Indian world for mathematics occurring in as early as the vedic period. ‘Patiganita’ means science of calculation on wooden board and it was used in India from the very early times. In olden times, when paper was not invented, figures were written on dust often called *Dhuti Karan* (Dust work), the Arabic equivalent being ‘llam hisab-al-takht’ and hisab-al- ghobar’ (calculation on dust).